Evaluasi Program Kinerja Badan Usaha Milik Desa (BUMDes) dalam Meningkatkan Kesejahteraan Masyarakat : Studi Desa Wulublolong Kecamatan Solor Timur Kabupaten Flores Timur - Veronika Noviana Raiina Koten; Made N. D. Andayana; Delila A. N. Seran; Nursalam Nursalam (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to evaluate the performance of Village-Owned Enterprises (BUMDes) in improving community welfare in Wulublolong Village, East Solor District, East Flores Regency. The research applies a qualitative descriptive approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, involving 11 informants selected using purposive sampling. The analysis employs the CIPP evaluation model (Context, Input, Process, Product) developed by Stufflebeam. The findings indicate that the implementation of BUMDes programs has not been optimal. From the context aspect, there are limitations in infrastructure, weak alignment of programs with community needs, and low community participation. From the input aspect, although initial capital is available, managerial capacity, planning, and financial management remain inadequate. From the process aspect, program implementation is not supported by effective supervision and evaluation mechanisms, resulting in the discontinuation of several business units. From the product aspect, BUMDes has not significantly contributed to increasing village income and community welfare, except for the gallon water business which remains sustainable due to its relevance to basic community needs. The study concludes that the main challenges of BUMDes lie in managerial weaknesses, limited human resource capacity, and lack of community involvement. Strengthening institutional capacity, improving management systems, and aligning business programs with local potential are necessary to enhance BUMDes performance and sustainability.